Take notes - Fry, Ronald W. (Hawthorne, NJ : Career Press, 1994)
Presents the essentials of a note-taking system that may help students identify and capture important information from teachers, textbooks, and resource materials.
Includes index.
Young Adult
Keywords: Note-taking.; Study skills